Hubungan Hukum Kemitraan antara Driver Online dengan Penyedia Layanan - Cahyono, Anton; Kusuma, Indra Fredika; Kusumo, Hendro Haryo (Perspektif Hukum, 2024)
This study aims to find the best way out to realize legal protection for Online Drivers. This study uses a normative legal research type.(legal research, rechtsonderzoek),by emphasizing the implementation of law and conceptual approaches, especially related to partnership agreements. This study is not intended to verify the hypothesis testing. Thus, legal research is not known for hypotheses, and also does not recognize the term data. In legal research, the term legal material is used. The results of this study indicate that there are fundamental differences between partnership agreements and work agreements. Moreover,The partnership relationship between online drivers and application service providers is basically unique, considering that the legal and formal positions of the parties are equal (see Article 36).Law Number 20 of 2008).However, socially and economically online drivers are in a weak position. Therefore, the government as the sovereign should provide legal protection for online drivers in the form of laws and public policies. Legal protection for online drivers is basically intended to protect their rights. This is in line with John Rawls' principle of distributive justice.